The Imperative of Development : The Wolfensohn Center at Brookings - Linn, Johannes F.; Kharas, Homi J., 1954-; Gertz, Geoffrey, 1984- (Book collections on Project MUSE., 2017)
The Imperative of Development highlights the research and policy analysis produced by the Wolfensohn Center for Development at Brookings. The Center, which operated from 2006 to 2011, was the first home at Brookings for research on international development. It sought to help identify effective solutions to key development challenges in order to create a more prosperous and stable world. Founded by James and Elaine Wolfensohn, the Center's mission was to "to create knowledge that leads to action with real, scaled-up, and lasting development impact." This volume reviews the Center's achievements and lasting legacy, combining highlights of its most important research with new essays that examine the context and impact of that research. Six primary research streams of the Wolfensohn Center's work are highlighted in The Imperative of Development: the shifting structure of the world economy in the twenty-first century; the challenge of scaling up the impact of development interventions; the effectiveness of development assistance; how to promote economic and social inclusion for Middle Eastern youth; the case for investing in early child development; and the need for global governance reform. In each chapter, a scholar associated with the particular research topic provides an overview of the issue and its broader context, then describes the Center's work on the topic and the subsequent influence and impact of these efforts. The Imperative of Development chronicles the growth and expansion of the first center for development research in Brookings's 100-year history and traces how the seeds of this initiative continue to bear fruit.